The effects of a standard elliptical vs. a modified elliptical with a converging footpath on lower limb kinematics and muscle activity. Issue 20 (17th October 2020) - Hummer, Erik; Murphy, Eryn; Suprak, David N.; Brilla, Lorrie; San Juan, Jun G.
ABSTRACT: Elliptical trainers that increase the inter-pedal distance may have potential benefits for knee osteoarthritis by decreasing the amount of knee varus. Modifying elliptical trainers with a converging footpath and reduced inter-pedal distance may be beneficial for reducing anterior knee pathology risk by decreasing knee valgus angles. Twenty-one college students participated in a single testing session. Participants exercised on two different elliptical trainers, one modified with a converging footpath and reduced inter-pedal width, and a standard elliptical trainer. Participants exercised for 2 min at three ramps incline at 120 strides per minute and constant work rate. Three-dimensional kinematics and electromyography of the dominant lower limb were recorded. Multiple 2 × 3 (Elliptical x Incline) ANOVAs with Bonferroni corrections were used to compare the two elliptical trainers at each incline for kinematics and muscle activity. The modified elliptical trainer displayed significantly decreased peak knee valgus ( p = 0.031, η p 2 = 0.234 ), peak knee flexion ( p = 0.006, η p 2 = 0.246 ), and interactions for peak knee flexion ( p = 0.001, η p 2 = 0.250 ) and vastus lateralis ( p < 0.01, η p 2 = 0.380 ) muscle activity compared to the standard elliptical trainer. The decreased peak knee valgus and flexion angles could be beneficial for reducing long-term injury risk for anterior knee pathologies.